Varicella vaccine in post-exposure prophylaxis - Ferson, Mark J (Communicable Diseases Intelligence, 2001)
Evidence concerning the effectiveness of Oka-based varicella vaccines when administered following exposure to varicella zoster virus in domestic and hospital settings is reviewed. The evidence appears to support post-exposure use of Oka-derived varicella vaccines in children within 3 days of rash onset in the index case. Despite vaccination, a small proportion will develop mild, but infectious, chickenpox, especially if they have been exposed in the household setting. Controlled studies of post-exposure prophylaxis in adults using both Varilrix and Varivax II are still needed. The applicability of this approach to disease control in health care facilities and in community settings warrants wider discussion. Commun Dis Intell 2001;25:13-15.